The work wife : a novel - Hart, Alison B. (Graydon House, 2022)
Three fierce women connected to a billionaire film mogul collide at a Hollywood party in this richly observed novel about female ambition, complicity, and privilege. Zanne Klein never planned to be a personal assistant to Hollywood royalty Ted and Holly Stabler. But a decade in at thirty-eight, that's exactly how she spends her days, earning six figures to make sure the movie mogul and his family have everything they could ever dream of and more. However, today is no ordinary day at the Stabler estate. Tonight, everyone who's anyone will be there for the Hollywood event of the season, and if the party's a success, that chief of staff job Zanne's been chasing may soon be hers. Which means she can buy a house, give her girlfriend the life she deserves, pay off her student loans. Northing's going to get in Zanne's way--not disgruntled staff, not a nosy reporter, not even a runaway hostess. But when Ted's former business partner, Phoebe Lee, unexpectedly shows up right before go time, Zanne suddenly has a catastrophe unfolding before her--one with explosive consequences. As the truth comes out and Zanne realizes how deeply entangled she's become in the Stablers' world, she must decide if the sacrifices she's made for the job are worth the moral price she has to pay.